Entropy analysis on energy-consumption process and improvement method of temperature/vacuum swing adsorption (TVSA) cycle. (15th July 2019) - Li, Shuangjun; Deng, Shuai; Zhao, Ruikai; Zhao, Li; Xu, Weicong; Yuan, Xiangzhou; Guo, Zhihao
Abstract: CO2 adsorption capture, which could be driven by various forms of energy, has been widely studied in recent years due to the equipment is easy to control with low energy consumption required. However, the existing research on the energy-efficiency aspects of temperature/vacuum swing adsorption (TVSA) for CO2 capture are primarily focus on the quantification of input energy in specific cases. As a classical concept in thermodynamics, entropy has been widely applied in researches on the energy conversion process, which could benefit an in-depth understanding on the mechanism of "heat-generalized chemical energy" conversion. However, an integrated thermodynamic research framework, which could clarify how to conduct a reasonable energy-consumption analysis of TVSA, has not been established yet. In this paper, a simplified thermodynamic cycle of 4-step TVSA was established, with the assumption of CO2 in adsorbed phase as loop fluid. With the application of the thermodynamic research framework proposed in this paper, the entropy analysis on the thermodynamic cycle was conducted. This study is concerned with application of thermodynamics concept to the CO2 adsorption engineering, which is mainly based on classical thermodynamics but also relying on adsorption physics to supply insight into the energy conversion and energy-efficient mechanism of TVSA technologies. Highlights: A simplified thermodynamic cycle is established for 4-step TVSA. The thermodynamic framework is proposed for entropy analysis on TVSA process. The effect of the main operating parameters and heat recovery on entropy-related indexes is evaluated.